SHM_122554_HST_3D Three-Legged Ceramic Pot (Broken) - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a fragment of a three-legged ceramic pot from the Middle Ages, collected in the field from Slottsfjärden in Kalmar and currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=659

Link to Sök I Samlingarna

https://samlingar.shm.se/object/18901805-D184-452A-AB3F-0B7410149FFB
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; Swedish Middle Ages; Slottsfjärden; Archaeology/history; History and archaeology; Dynamic Collections; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi